Streetlamp with novel laser source - XIA ZEQIANG (2018)
The invention belongs to the technical field of lighting, and particularly relates to a streetlamp with a novel laser light source. The streetlamp comprises a lamp body structure of the streetlamp andthe light source, the light source is a light emitting device capable of being subject to laser excitation to be converted into white light, a laser emission device and a light conversion medium areincluded, the laser emission device sends out blue laser, the blue laser is subject to excitation conversion into white light through the light conversion medium, the optical wavelength of the blue laser ranges from 420 nm to 470 nm, and the light conversion medium can be one of glass, transparent ceramic and a single crystal. 本发明属于照明技术领域，具体涉及种具有新型激光光源的路灯，包括路灯的灯体结构和光源，所述光源为种受激光激发转化成白光的发光装置，包括激光发射装置和光转换介质，所述激光发光装置发出蓝光激光并通过光转换介质后激发转化成白光，所述蓝光激光的光波长为420-470nm之间；所述光转换介质可以为玻璃、透明陶瓷、单晶中的任种。